2013
DOI: 10.1021/am404344h
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of In Situ Streptococcus mutans Biofilms

Abstract: Insight into live microbial biofilm microstructure and mechanical properties and their interactions with the underlying substrate can lead to the development of new remedial strategies and/or materials. Here we report mechanical properties of dental pathogenic Streptococcus mutans biofilms, grown on a polystyrene-coated plate of a shear rheometer in physiologically relevant conditions, precisely controlled in a custom built bioreactor. In situ measurements demonstrated the importance of microstructure and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Previous work has determined the mechanical properties of biofilms through various methods. 21,22 The elastic modulus ( G ′) of S. epidermidis biofilms, found through mechanical rheometry, varies widely, from 1 Pa to 8 kPa, depending on factors such as growth conditions and analytical methods. 2330 Under conditions that most resemble those in which S. epidermidis biofilms cause disease, Pavlovsky et al 31 determined that G′ is approximately 10 Pa.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has determined the mechanical properties of biofilms through various methods. 21,22 The elastic modulus ( G ′) of S. epidermidis biofilms, found through mechanical rheometry, varies widely, from 1 Pa to 8 kPa, depending on factors such as growth conditions and analytical methods. 2330 Under conditions that most resemble those in which S. epidermidis biofilms cause disease, Pavlovsky et al 31 determined that G′ is approximately 10 Pa.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has indicated that the biophysical properties of S. mutans biofilms can be varied depending on the exopolysaccharide content, due to its viscoelastic characteristics similar to those of polymeric substances (Vinogradov et al 2004;Cense et al 2006;Waters et al 2014). The elastic (or storage) modulus of S. mutans biofilms was associated with the amount of exopolysaccharides (Waters et al 2014), while the tensile strength of the biofilms was predominantly determined by the tensile strength of the EPS matrix (Cense et al 2006). The present rheological data provide further support for the importance of exopolysaccharides in the viscoelastic properties and cohesiveness of the biofilm.…”
mentioning
confidence: 99%
“…These structural changes may affect the stability of the biofilms treated with αMG and facilitate mechanical clearance of biofilms. The mechanical stability of biofilms appears to be dependent on the exopolysaccharide content, as EPS binds the cells together while strengthening their cohesiveness [15] , [47] [50] . Furthermore, glucans enhance S. mutans adhesive strength, while the development of multi-microcolony aggregates via EPS-cell adhesions provides structural integrity to S. mutans biofilms [16] , [18] .…”
Section: Resultsmentioning
confidence: 99%